2017
DOI: 10.37469/0507-3758-2017-63-2-329-335
|View full text |Cite
|
Sign up to set email alerts
|

Harmonized Statistical Analysis of the Efficacy of Intraperitoneal Chemotherapy Regimens With Dioxadet on Ascitic Ovarian Cancer Model

Abstract: A comparative statistical study of the results of eight independent experiments on the efficacy of intraperitoneal chemotherapy has been performed. The regiments of cathether intraperitoneal chemotherapy (CIPC), normothermic and hyperthermic chemoperfusion (NIPEC and HIPEC) with antitumor drug dioxadet were investigated in 288 female Wistar rats with ascitic ovarian cancer. Ovarian cancer was transplanted intra-peritoneally (i.p.) 48 hours prior to a single chemotherapy at a number of 1*107 tumor cells. Dioxad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Varying the substituents at the heterocycle (triazine) allows to change the properties of the compound [8] with potentially advantageous medical effects. Substance (a) was synthesised, investigated, and subsequently approved for medical use in the 1980s as an antineoplastic agent for the treatment of ovarian, breast, lung, kidney, liver cancers and for the prevention of regional metastasis in oral cancer [9][10][11][12]. In [13] it was shown that substance (a) is effective against abdominal carcinomatosis in animals.…”
Section: Introductionmentioning
confidence: 99%
“…Varying the substituents at the heterocycle (triazine) allows to change the properties of the compound [8] with potentially advantageous medical effects. Substance (a) was synthesised, investigated, and subsequently approved for medical use in the 1980s as an antineoplastic agent for the treatment of ovarian, breast, lung, kidney, liver cancers and for the prevention of regional metastasis in oral cancer [9][10][11][12]. In [13] it was shown that substance (a) is effective against abdominal carcinomatosis in animals.…”
Section: Introductionmentioning
confidence: 99%